Silk fibroin-alginate based beads for human mesenchymal stem cell differentiation in 3D. (5th September 2019) - Patil, Smita; Singh, Neetu
Abstract : Silk fibroin alginate beads support proliferation of hMSCs and induce differentiation solely due to functional groups within 14 days. Abstract : Lately silk fibroin has gained a lot of popularity as a tissue engineering scaffold due to its exceptional mechanical properties, negligible inflammatory reactions, remarkable biocompatibility, and tunable biodegradability. Nonetheless, 3 dimensional (3D) silk fibroin based scaffolds, which allow simultaneous formation of scaffolds and cell encapsulation with minimal damage to the cells, are unavailable, as most of the methods involve the use of some cell destructive techniques. Thus, cells have to be loaded after the scaffold formation and the study has to rely upon the ability of the cells to penetrate the scaffold to obtain a 3D microenvironment. Hence, these platforms do not allow for a true 3D system replicating the in vivo environment. Here silk fibroin-alginate based beads have been developed, and retain silk fibroin for a longer period of time and allow for simultaneous cell encapsulation as the crosslinking method is cell-compatible. It is demonstrated for the first time that these silk fibroin-alginate beads can be used to encapsulate the cells at varying cell densities depending on the desired application. These beads were further used to study the effect of functional groups on human mesenchymal stem cell (hMSC) differentiation in 3D, by utilizing carboxylic groups naturally present in alginate as well as introducing phosphate groups. The results showed that these beads were able to support the growth and proliferation of hMSCs and induced differentiation solely due to functional groups within 14 days. These beads were better in directing hMSC differentiation into osteogenic and chondrogenic lineages compared to 2D surfaces and differentiation media.